Analysis of Factors Influencing the Availability of Medicine During JKN Era - Satibi Satibi; Ranowijaya Ranowijaya; Aswandi Aswandi; Junagsti Bermalam; Gunawan Pamudji Widodo (Indonesian Journal of Pharmacy, 2018)
The availability of medicine is important during National Social Healthy Insurance (JKN) that put into effect in the hospital, one of health service facility. The purpose of this study was to look of the availability of medicines was during JKN era and what factors influence the availability in three Region General Hospitals in Sulawesi. This study was conducted using descriptive method of analytic to get a correlation among doctors, pharmacists and patients as independent variables toward the availability of medicine as dependent variable. The study has been performed in 3 hospitals in Sulawesi. This data obtained were analyzed using statistical model of Linier Regression Analysis with F test or ANOVA test and t test. R was the value of regression which showed the influence of one to another variable. The results showed the level of medicine availability in hospital A was 12.49 months. Factors that influence the availability of medicines were doctors (R=0.778, p= 0.000), pharmacists (R=0.619, p= 0.000) and patients (R=0.653, p= 0.000). All there factor significantly affect the availability of medicines in Hospital A (R=0.675, p=0.000). Hospital B had an excess supply of medicines, with the average of 23.31 month. Factors that influenced the availability of medicines in Hospital B was doctor (R=0.877), pharmacist (R=0.861) and patient (R=0.984) (p=0.000 all). From multiple regression there factors showed a significant correlation to the availability of medicines (R=0.901, p=0.000). Similarity on Hospital A and B, data of the availability of medicine in hospital C was categorized excess as the average of stock was 56.01 month. Factors that influenced the availability of medicines in Hospital C was doctor (R=0.753, p= 0.000), pharmacist (R=0.869, p= 0.000) and patient (R=0.545, p=0.001).